Evaluation of faciocutaneous clues to systemic diseases: A learning module for Chinese undergraduate medical students - Zhu Shen; Ling Chen; Wenying Liu; Xue Lv; Guochun Xiang (Wolters Kluwer Medknow Publications, 2016)
Background: Medical students will encounter cutaneous lesions associated with systemic disorders during their training and career. However, there are no chapters in Chinese undergraduate medical textbooks regarding these lesions. Objective: The objective of the present study was to evaluate the impact of an additional learning module about cutaneous lesions associated with systemic disorders for Chinese undergraduates. Methods: In this medical course, we introduced a case-based clinical learning module. This module was evaluated with a pre-/postcourse questionnaire and a final multichoice examination. Results: After learning, more students agreed that some skin lesions could serve as "windows" to hidden systemic diseases, and it was more important to learn how to distinguish lesions associated with systemic diseases from simplex ones. We found that the group that was provided conventional teaching plus this module scored significantly better (52.75 ± 23.96) than the conventional teaching group (40.53 ± 21.43; t = 2.370, p = 0.020) in the final multichoice examination. Conclusion: Introducing this additional learning module may offer an early opportunity to explore systemic diseases from a dermatological view and is likely to lay the foundations for interdisciplinary collaboration in the future practice for medical students.